The migration of alkali metal (Na + , Li + , and K + ) ions in single crystalline vanadate nanowires: Rasch-Hinrichsen resistivity - Lee, Yejung; Ye, Byeong Uk; Lee, Dong Kyu; Baik, Jeong Min; Yu, Hak Ki; Kim, Myung Hwa (Current Applied Physics, 2019)
We report the synthesis of single crystalline alkali metal vanadate nanowires, Li-vanadate (Li 4 V 10 O 27 ), Na-vanadate (NaV 6 O 15 ), and K-vanadate (KV 4 O 10 ) and their electrical properties in a single nanowire configuration. Alkali metal vanadate nanowires were obtained by a simple thermal annealing process with vanadium hydroxides(V(OH) 3 ) nanoparticles containing Li + , Na + , and K + ions and further the analysis of the migration of charged particles (Li + , Na + , and K + ) in vanadate by measuring the conductivity of them. We found that their ionic conductivities can be empirically explained by the Rasch-Hinrichsen resistivity and interpreted on the basis of transition state theory. Our results thus indicate that the Li ion shows the lowest potential barrier of ionic conduction due to its small ionic size. Additionally, Na-vanadate has the lowest ion number per unit V 2 O 5 , resulting in increased distance to move without collision, and ultimately in low resistivity at room temperature.
Keywords: Ionic sizes; Low resistivity; Per unit; Potential barriers; Single nanowires; Single-crystalline; Thermal annealing process; Transition state theories; Alkali metal vanadate; Ionic conductivity; Nanowires; Rasch-Hinrichsen resistivity